2017
DOI: 10.18632/oncotarget.17704
|View full text |Cite
|
Sign up to set email alerts
|

BRAF/MEK inhibitors promote CD47 expression that is reversible by ERK inhibition in melanoma

Abstract: The expression of CD47 on the cancer cell surface transmits “don’t eat me” signalling that not only inhibits phagocytosis of cancer cells by phagocytes but also impairs anti-cancer T cell responses. Here we report that oncogenic activation of ERK plays an important role in transcriptional activation of CD47 through nuclear respiratory factor 1 (NRF-1) in melanoma cells. Treatment with BRAF/MEK inhibitors upregulated CD47 in cultured melanoma cells and fresh melanoma isolates. Similarly, melanoma cells selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…BRAF inhibitor resistance involves a range of transcription factors ( Table 2 ) [ 14 , 16 , 22 , 28 , 45 , 46 , 48 , 52 , 58 , 66 , 81 , 89 , 97 , 117 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ]. A transcriptomic analysis of BRAF inhibitor-resistant melanoma cells showed that some transcription factors were upregulated whereas others were downregulated [ 141 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BRAF inhibitor resistance involves a range of transcription factors ( Table 2 ) [ 14 , 16 , 22 , 28 , 45 , 46 , 48 , 52 , 58 , 66 , 81 , 89 , 97 , 117 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ]. A transcriptomic analysis of BRAF inhibitor-resistant melanoma cells showed that some transcription factors were upregulated whereas others were downregulated [ 141 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the tumor cell, this reversion to a low immunogenic state is caused by induced expression of programmed cell death ligand-1 (PD-L1) [ 165 , 166 , 167 , 168 , 169 ], increased expression of the immunoregulatory protein Galactin-1 [ 170 ], and increased expression of CD47, an immunoregulatory cell marker, on tumor cells, leading to reduced killing by cytotoxic T-cells and macrophages [ 133 ]. BRAF inhibitor-resistant tumor cells also show reduced expression of target antigens [ 164 ], and increased production of IL-10 [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Melanoma is the highly aggressive skin cancer with mounting incidence over the past 30 years, which is associated with early metastasis, late diagnosis, and tolerance to chemotherapy in advanced stages [ 1 ]. The emergence of some novel therapies against melanoma such as genetically targeted therapies (e.g., BRAF inhibitors) and immunotherapies (e.g., PD-1/PD-L1 and CTLA-4 antibodies) has undoubtedly improved melanoma treatment, but the overall prognosis of patients remains poor [ 2 , 3 ]. Therefore, it is urgently required to discover novel targets and develop more effective and lasting therapeutic strategies for melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…Its activation is subsequent to phosphorylation and relocation from the cytoplasm to the nucleus. (Liu et al, 2017) Studies aiming to understand the role of Thrombospondin-1 (TSP1) have helped in understanding the role played by CD47. TSP1 is a large, secreted glycoprotein.…”
Section: Pathophysiological Mechanisms Of Cardiovascular Toxicity Of mentioning
confidence: 99%